Basic Predictive Risk Factors for Cytokine Storms in COVID-19 Patients - Shcherbak, Sergey G.; Anisenkova, Anna Yu; Mosenko, Sergei V.; Glotov, Oleg S.; Chernov, Alexander N.; Apalko, Svetlana V.; Urazov, Stanislav P.; Garbuzov, Evgeny Y.; Khobotnikov, Dmitry N.; Klitsenko, Olga A.; Minina, Evdokia M.; Asaulenko, Zakhar P. (Frontiers in Immunology, 2021)
Objective: A critical role in COVID-19 pathogenesis is played by immune dysregulation that leads to a generalized uncontrolled multisystem inflammatory response, caused by overproduction of proinflammatory cytokines, known as ‘a cytokine storm’ (CS), strongly associated with a severe course of disease. The aim of this study is to identify prognostic biomarkers for CS development in COVID-19 patients and integrate them into a prognostic score for CS-associated risk applicable to routine clinical practice. Materials and methods. The authors performed a review of 458 medical records from COVID-19 patients (241 men and 217 women aged 60.0±10.0) who received treatment in the St. Petersburg State Budgetary Institution of Healthcare ‘City Hospital 40 (City Hospital 40, St. Petersburg), from Apr. 18, 2020 until Nov. 21, 2020. The patients were split in 2 groups: one group included 100 patients with moderate disease symptoms; the other group included 358 patients with progressive moderately severe, severe, and extremely severe disease. The NEWS (National Early Warning Score) score was used alongside with clinical assessment, chest computed tomographic (CT) scans, electrocardiography (ECG), and lab tests, like ferritin, CRP, IL-6, lactate dehydrogenase (LDH), D-dimer. Results: The basic risk factors for cytokine storms in COVID-19 patients are male gender, age over 40y., positive test result for replicative SARS-CoV-2 RNA, absolute lymphocyte count, dynamics in the NEWS score, as well as LDH, D-dimer, ferritin, and IL-6 levels. These clinical and instrumental findings can be also used as laboratory biomarkers for diagnosis and dynamic monitoring of cytokine storms. The suggested prognostic scale (including the NEWS score dynamics; serum IL-6 greater than 23 pg/ml; serum CRP 50 mg/L or greater; absolute lymphocyte count less than 0.72×109/L; positive test result for replicative coronavirus (SARS-CoV-2) RNA; age 40y. and over) is a useful tool to identify patients at a high risk for cytokine storm, requiring an early onset of anti-inflammatory therapy.